Plankton Community Structure as a Bioindicator of Lake Toba Water Conditions in Balige District Toba Regency - Ewin Handoco; Welmar Olfan Basten Barat (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Plankton sampling was conducted at three observation stations in the study area, with samples collected from surface waters using standard plankton sampling techniques. Phytoplankton and zooplankton were identified microscopically, and community structure was evaluated using abundance, diversity (Shannon-Wiener), evenness, and dominance indices. A total of six phytoplankton classes and four zooplankton classes were identified. The phytoplankton community was represented mainly by members of Bacillariophyceae, Chlorophyceae, Cyanophyceae, Dinophyceae, Coscinodiscophyceae, and Zygnematophyceae, while the zooplankton community was dominated by taxa belonging to Crustacea, Rotatoria, Hexanauplia, and Tubulinea. Phytoplankton species richness was higher than zooplankton richness, indicating a relatively stable aquatic ecosystem with a well-developed primary producer community. Phytoplankton abundance ranged from 709,652 to 2,414,621 cells m⁻³ across stations, whereas zooplankton abundance ranged from 51,119 to 300,700 individuals m⁻³. The Shannon-Wiener diversity index (H′) showed moderate diversity (1 ≤ H′ ≤ 3), suggesting sufficient productivity, fairly balanced ecosystem conditions, and moderate ecological pressure. Evenness values indicated a relatively uniform distribution of plankton among sampling stations, while dominance index values showed that no single taxon dominated the community. The plankton community structure suggests that the study area remains in a relatively stable ecological condition and supports balanced aquatic ecosystem functioning.